Usposabljanje gluhih s pomočjo polževega vsadka - naše izkušnje - Vatovec, Jagoda (Zdravniški vestnik, 2005)
Background. The hearing impairment has an impact on the persons capabilities and has an influence on the quality of life. In the early childhood the acoustic information is indispensable for development of speech and language. The cochlear implant is a biomedical device that enables the deaf to hear but it cannot help all the hearing impaired individuals. Patients and methods. In the period from March 1996 to August 2004 there were 110 deaf patients who were operated on for cochlear implantation. We evaluated the ethiologic factors of deafness, the age at onset of deafness and the benefits of cochlearimplant use. Results. Most of the implanted patients were congenitallydeaf (60.91%). The most frequent cause of deafness was hereditary hearing loss (30.00%). The period of deafness was in majority (52.72%) less than five years but a few (10.00%) were deaf for more than 15 years. Reimplantation was necessary in four patients. The application and the benefits vary between the individuals but only two gave up the implant all theremainders use it every day. The communication mode in 88 patients is acoustic-oral while in 22 subjects a total method is used. Conclusions. The outcome of management of deafness by cochlear implants is comparable to other centers. Good results in congenitally deaf children support the need for universal neonatal hearing screening.
Keywords: Cochlear Implant; Deafness; Gluhost; Govor, zaznava; hearing; kohlearni implant; okvara sluha; rehabilitacija; sluh; Speech Perception; sporazumevanje; therapy; Treatment Outcome; vocational rehabilitation; zdravljenje; Zdravljenje, izid